POST-OPERATIVE SIMPLE INCOMPLETE ACQUIRED SYNDACTYLY IN THIRD AND FOURTH DIGITI MANUS SINISTRA: A CASE REPORT - Zevanya, Evita; Zacharias, Samuel (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Syndactyly is interdigiti soft tissue and/or osseous fusion or adhesion and may affect hand and/or foot. Syndactyly is caused by congenital or acquired. Acquired syndactyly is a rare disease that may caused by trauma, inflammation, or infection around the finger. This abnormality may affect aesthetic and functional impairment, so that surgery procedure is needed to syndactyly release. The aim of this paper is to report a rare case of simple incomplete acquired syndactyly post-operative in a man aged 53 year old. Patient came to surgery clinic because adhesion of his third and fourth left hand fingers since 21 years ago. The abnormality was disturbing his work as a baker currently. He had trauma 21 years ago when he worked as construction labour that cause swelling in his left palm, so he went to hospital and got needle aspiration. After needle aspiration, he experienced worse symptoms like recurrency swelling, rednesss, itchy, and pain then got surgery procedure that did not affect the fingers area directly. After surgery, the symptoms got improved, but he found adhesion between his third and fourth fingers days later after surgery. From currently physical examination, there was left hand interdigiti adhesion between 1/3 proximal thirth and forth fingers and from palpation there was no adhesion between the finger bone. He was diagnosed simple incomplete acquired syndactyly third and fourth digiti manus sinistra. The patient got surgery procedure with z-plasty technique to syndactyly release and hospitalized for 3 days. He got Cefixime, Ketoprofen, and Mefenamic Acid when he went home. The patient came to hospital to get follow-up 6, 10, and 17 days after surgery. Keywords: Simple incomplete acquired syndactyly; post-operative; case report.